Flourishing: Development of a Higher-Level Uses Well-Being Scale and Concept in Positive Psychology - Nur'aini, Nadja Alfin; Mulyana, Olievia Prabandini (Universitas Negeri Surabaya, 2024)
Background: Flourishing is the highest level of well-being in positive psychology. Flourishing individuals have high levels of well-being based on hedonic and eudaimonic well-being perspectives. Flourishing is a developing concept that has yet to be widely studied in positive psychology. Objective: This literature review aims to trace the development of theoretical concepts and scales that can be used to research the flourishing variable further. Methods: This research uses a literature review, which involves searching reputable journals for articles related to the concept and scale of flourishing. Results: The PERMA concept introduced by Seligman is the primary literature that forms the foundation for examining flourishing by combining two theories. This PERMA concept states that flourishing in individuals can be measured by five aspects: positive emotions, engagement, positive relationships, meaningfulness, and individual achievement. Conclusion: Other researchers then developed the PERMA concept as a reference for creating a flourishing scale. Keywords: Flourishing, well-being, theory, scale, literature review